Quasi-maximum exponential likelihood estimation for a non stationary GARCH(1, 1) model. Issue 4 (16th February 2016) - Pan, Baoguo; Chen, Min
ABSTRACT: This article investigates a quasi-maximum exponential likelihood estimator(QMELE) for a non stationary generalized autoregressive conditional heteroscedastic (GARCH(1, 1)) model. Asymptotic normality of this estimator is derived under a non stationary condition. A simulation study and a real example are given to evaluate the performance of QMELE for this model.